INFLUENCE OF EXTERNAL MAGNETIC FIELD ON THE RATE OF CHEMICAL REACTIONS AT BURNING BIOFUELS - Kozhevnikov, Y.; Nikolaev, V. (Енергетика і автоматика, 2016)
This article discusses the theoretical basis of the use of control substances spins of valence electrons of the fuel mixture in solving problems to improve the quality of combustion and catalytic acceleration of chemical reactions (spin catalysis).